2004
DOI: 10.1523/jneurosci.2034-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Epilepsy Mutation in the Sodium ChannelSCN1AIdentifies a Cytoplasmic Domain for β Subunit Interaction

Abstract: A mutation in the sodium channel SCN1A was identified in a small Italian family with dominantly inherited generalized epilepsy with febrile seizures plus (GEFSϩ). The mutation, D1866Y, alters an evolutionarily conserved aspartate residue in the C-terminal cytoplasmic domain of the sodium channel ␣ subunit. The mutation decreased modulation of the ␣ subunit by ␤1, which normally causes a negative shift in the voltage dependence of inactivation in oocytes. There was less of a shift with the mutant channel, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
142
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 76 publications
15
142
1
Order By: Relevance
“…In addition to its role in channel inactivation, the C‐terminal domain of Na v 1.6 interacts with several proteins that regulate channel trafficking or activity 20, 23, 30. To determine whether mutations at Arg1872 disrupt these interactions, we tested the effect of the p.Arg1872Trp mutation with substitution of the large uncharged tryptophan residue.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its role in channel inactivation, the C‐terminal domain of Na v 1.6 interacts with several proteins that regulate channel trafficking or activity 20, 23, 30. To determine whether mutations at Arg1872 disrupt these interactions, we tested the effect of the p.Arg1872Trp mutation with substitution of the large uncharged tryptophan residue.…”
Section: Resultsmentioning
confidence: 99%
“…␤2 and ␤4 subunits are covalently linked to the ␣ subunit by disulfide bridges (dashed-dotted line), but the cysteine residues implicated have not been identified yet. ␤1 and ␤3 subunits have noncovalent intracellular and extracellular interactions with the ␣ subunit (dashed lines) (McCormick et al, 1998;Qu et al, 1999;Meadows et al, 2001;Spampanato et al, 2004). M1841T lies in a 41-residue area, highlighted in the inset, comprising a cytoplasmic binding domain for ␤1 and, probably, ␤3 (Spampanato et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…␤1 and ␤3 subunits have noncovalent intracellular and extracellular interactions with the ␣ subunit (dashed lines) (McCormick et al, 1998;Qu et al, 1999;Meadows et al, 2001;Spampanato et al, 2004). M1841T lies in a 41-residue area, highlighted in the inset, comprising a cytoplasmic binding domain for ␤1 and, probably, ␤3 (Spampanato et al, 2004). The GEFSϩ mutation D1855Y (Spampanato et al, 2004) is also shown in the inset; we used a different numeration than the original D1866Y, because the clone that we used codifies for a shorter hNa v 1.1 variant (see Results).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations